PENINGKATAN KEMAMPUAN GURU DALAM MEMBUAT MEDIA PEMBELAJARAN MELALUI TEKNIK SUPERVISI BERKELOMPOK BERBASIS DISKUSI DI SDN 28 SIMPANG - Elida, Elida (Jurnal Manajemen Pendidikan, 2018)
Based on observations on the ability of the teacher of SDN 28 Simpang in making learning media in the phenomenon found that the ability of teachers to make learning media is still low. The purpose of this study was to describe and obtain information about improving the ability of teachers to make learning media through Discussion-Based Group Supervision Techniques at Simpang SDN 28. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 5 teachers at SDN 28 Simpang. Research data was collected using an observation sheet. Data is analyzed using percentages. Based on the results of research and discussion, it can be concluded that Through Discussion-Based Group Supervision Techniques can improve the ability of teachers in making learning media at SDN 28 Simpang. Analysis of the quality of learning media (teaching materials and slide presentations) made by the teacher shows that the teacher's ability to make learning media increases from cycle I to cycle II. The ability of teachers to make learning media in cycle I is 79.00 (enough) to increase to 84.40 (good) in cycle II.